Patella instability in the skeletally immature patient: pearls for surgical treatment - Andrish, Jack (Annals of Joint, 2018)
The surgical management of patella instability has evolved over time to become an “al a carte” menu of surgical options to address the numerous pathoanatomies which predispose to recurrent patella dislocations and subluxations. The challenge when managing patella instability in the skeletally immature patient relates to the presence of open growth plates which can be subject to iatrogenic injury. That said, most often these challenges can be overcome and lead to successful outcomes. This section will present a series of “pearls” to consider when preparing a surgical plan of action for the care of children and youth with recurrent patella subluxations and dislocations.